Site Locating For Inspection Posts of Freight Cars in Railway Network Using Analytical Hierarchy Process (AHP) and Geographic Information System (GIS) (CaseStudy: Iranian Railway Network) - Saeed Monajjem; Mohammad Mahanpoor; Mohammad Sadathoseini (Civil Engineering Journal, 2015)
Freight car inspection and maintenance system have an undeniable role in total costs imposed on system for repair and rehabilitation process of different components of it. This issue shows its importance when railway transportation comes to competition with other modes of transportation. In this competition, lower total cost means more demands and more benefits for optimum systems. Using preventive maintenance methods for rolling stock are among appropriate solutions in order to lower the costs. These methods require to have an exact monitoring system to achieve a reliable scope of system. Inspection posts play an essential role as “wise eyes” on inspection system.Using Analytical Hierarchy Process (AHP) in this article has developed decision tree including goals, criteria, sub criteria and alternatives. The main criteria are 1-traffic, 2-geographical position, 3-loction of station on railway network, and 4-repair and maneuver equipment of station. These criteria and sub criteria have been weighted and quantified using expert’s opinion. The use of Geographical information system, 403 stations had been evaluated with 26 criteria and sub criteria and prioritized. By considering coverage of network in next step, 43 stations are recommended as required station numbers in railway network to provide 70.53% Coverage of railway network traffic.